Partitioning of Holocene kinematics and interaction between the Theistareykir Fissure Swarm and the Husavik-Flatey Fault, North Iceland. (February 2016) - Tibaldi, A.; Bonali, F.L.; Einarsson, P.; Hjartardóttir, Á.R.; Pasquarè Mariotto, F.A.
Abstract: Our research is aimed at contributing to the general understanding of how transform-rift junctions work, a topic that can be studied in exceptional detail in North Iceland, where the active transform Husavik-Flatey Fault (HFF) connects with the Gudfinnugja Fault (GF), the westernmost structure of the Theistareykir Fissure Swarm (TFS). We studied in the field: i) offsets along the easternmost HFF, ii) the geometry and kinematics of 649 faults and 1208 tension fractures in the TFS, iii) the interactions among all these structures. The HFF transtensional kinematics is compatible with the GF, which shows different offsets north and south of the junction between these two faults. We suggest the possible prolongation of the HFF beyond the junction, based on: i) the change in offsets and strikes of TFS normal faults, ii) the presence of en-échelon, NNW-SSE-striking normal faults and tension fractures with a slight right-lateral component, iii) the transition of some of the faults into tension fractures north of the prolongation of the HFF, and iv) the decrease in the cumulated offset of all the faults north of the HFF prolongation. We interpret these data as field evidence of the first stages of propagation of the HFF upward or across the TFS: This has clear implications for defining the potential rupture length of the HFF and, hence, for seismic hazard assessment. Highlights: We characterized the long-term Holocene kinematics of the major structures in the TFS. We mapped 649 fault scarps and 1208 tension fractures in the TFS. We systematically measured Holocene fault offsets and fracture opening directions. We looked into the possible prolongation of the HFF east of the junction with the TFS. We provided clues into the first stages of propagation of the HFF across the TFS.